(3eYLe GdCeKGd GdTYHjI aj eOf GdMLGR (B: s (3ecI GdecQeI hGdeOjfI GdefhQI hLOI NUhUG (B/s - (3SdGeI, aQjO YHO GdMejOs ((3LOI (B[(3GdSYhOjI(B] :s (3OGQ GdedJRe ddWHGYI hGdfTQ hGdJhRjY,s, 2020)
(3aj gPG GdcJGH JhKjb hJSLjd deYXe eG jNU GdMLGR hScGf eOfg, hgh TGed dcd eG gh MLGRj jJfGhd fhGMjge hCecfJge hYGOGJge hJbGdjOge hWQb eYjTJge hcd eG cGf ef HjfgG CeKGdge jTJed Ydi cd jbhdhfg Ch jfWbhf Hg Ch jaYdhg hbGFeI WhjdI LOG JOd Ydi CfeGW JacjQge hWQjbI eYGdLJge HGdEVGaI Edi GdCeKGd GdYGeI deOf GdMLGR(B. (3hbO ChdhG GdCeKGd YfGjI aGFbI dG JNai Ydi CMO, hjOQc Pdc YfO NQhL GdeKd ef CahGgge YfO cHGQ GdSf aJLO (B"(3EjLGR GddaX, hEUGHI GdeYfi hMSf GdJTHjg(B" (3MJi jNGd dc Cf eMOKc ef cHGQge jeS TZGa bdHc HcdGeg hbO GMJhi gPG GdcJGH Ydi Mce hJLGQH hCeKGd YOjOI ef LejY GdCLfGS MLGL heYJeQjf heLGhQjf(B.s
(3cTGa (B: (3UaMI (B691-742.s
Keywords: (3GdCeKGd GdYGejI GdYQHjIs -- (3GdSYhOjIs -- (3GdMLGRs -- (3eYGLes; (3GddZI GdYQHjIs -- (3dgLGJs -- (3GdSYhOjIs -- (3GdMLGRs -- (3eYGLes; (3GdCOH GdTYHj GdYQHjs -- (3GdSYhOjIs -- (3GdMLGRs -- (3eYGLes